Basic procedures for agroeconomic research (International rice research institute, 1991)
The book revised methods for economic analysis of cropping systems which was developed between 1975 and 1981. It offers analytical procedures that is usefull to interested agroeconomic researchers. It contains parts of the earlier work, but largely comprises new perspectives on basic procedures for economic analysis by field-level researchers. Reports of those reviews are contained in the report series of the Cropping Systems Working Group